Pengelolaan Bank Sampah Dengan Pendekatan Edukatif Dan Partisipatif Pada Lingkungan Sekolah - Suherman; Haris Triono Sigit; Media Sucahya; Sulasno (CV. Multi Kreasi Media, 2026)
The issue of waste management in educational environment is a global challenge, including in Indonesia. A study at Al-Araaf Education Foundation Cilegon identified main problems: low student understanding of waste management and limited supporting facilities at school. As a solution, the Community Service (PkM) team of Serang Raya University implemented a School Waste Bank program using an educative-participatory approach, which included socialization, regular waste collection, and implementation of the 3R (Reduce, Reuse, Recycle) principle. The results show an increase in environmental awareness and positive waste management habits. Participatory strategies such as hands-on activities, visual media, educational games, and a reward system proved effective in boosting student enthusiasm. The program successfully synergized educational, environmental, and economic aspects through the sale of inorganic waste. This model is recommended for replication in other educational institutions to support waste reduction in Cilegon City, which reaches 245 tons per day, and to achieve the national target of 30% waste reduction.